Symbol

# Calculator search results

Formula
Solve the equation
Graph
$y = \dfrac { 2 } { 3 } x + \dfrac { 1 } { 6 }$
$y = \dfrac { 1 } { 2 } x$
$x$Intercept
$\left ( - \dfrac { 1 } { 4 } , 0 \right )$
$y$Intercept
$\left ( 0 , \dfrac { 1 } { 6 } \right )$
$x$Intercept
$\left ( 0 , 0 \right )$
$y$Intercept
$\left ( 0 , 0 \right )$
$\dfrac{ 2 }{ 3 } x+ \dfrac{ 1 }{ 6 } = \dfrac{ 1 }{ 2 } x$
$x = - 1$
 Solve a solution to $x$
$\color{#FF6800}{ \dfrac { 2 } { 3 } } \color{#FF6800}{ x } + \dfrac { 1 } { 6 } = \dfrac { 1 } { 2 } x$
 Calculate the multiplication expression 
$\color{#FF6800}{ \dfrac { 2 x } { 3 } } + \dfrac { 1 } { 6 } = \dfrac { 1 } { 2 } x$
$\dfrac { 2 x } { 3 } + \dfrac { 1 } { 6 } = \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ x }$
 Calculate the multiplication expression 
$\dfrac { 2 x } { 3 } + \dfrac { 1 } { 6 } = \color{#FF6800}{ \dfrac { x } { 2 } }$
$\color{#FF6800}{ \dfrac { 2 x } { 3 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 6 } } = \color{#FF6800}{ \dfrac { x } { 2 } }$
 Multiply both sides by the least common multiple for the denominators to eliminate the fraction 
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \right ) \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ 3 } \color{#FF6800}{ x }$
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \right ) + 1 = 3 x$
 Get rid of unnecessary parentheses 
$\color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ x } + 1 = 3 x$
$\color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ x } + 1 = 3 x$
 Simplify the expression 
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } + 1 = 3 x$
$4 x + 1 = \color{#FF6800}{ 3 } \color{#FF6800}{ x }$
 Move the variable to the left-hand side and change the symbol 
$4 x + 1 \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = 0$
$4 x \color{#FF6800}{ + } \color{#FF6800}{ 1 } - 3 x = 0$
 Move the constant to the right side and change the sign 
$4 x - 3 x = \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = - 1$
 Organize the expression 
$\color{#FF6800}{ x } = - 1$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture